Kajian Pengeringan pada Pengering Tipe Rak dengan Konveksi Panas dari Pipa yang Dialiri Air Panas Geothermal - Yedi Gunawan; Yazid Ismi Intara; Bosman Sidebang; Ulfah Anis (Newton-Maxwell Journal of Physics, 2024)
This research aims to obtain the temperature performance of heat convection from hot water flow in pipes in the drying chamber during the drying process. This research method descriptively examines the drying function and the hot air flow process in the drying system. The results obtained from the research show that the average temperature in the drying room is 37oC while the temperature outside the dryer (environmental temperature) is 22oC. To dry 2 mm thick cassava slices from an ingredient weight of 23 g to 8 g, it takes 8-10 hours. The longer the drying time, the lower the moisture ratio value. An increase in temperature affects a decrease in the moisture ratio in geothermal hot water flow dryer. The decrease in the moisture ratio value was influenced by the decrease in the water content of the material during the drying process. The distribution of temperature movements that occur in the drying room at the beginning of the drying process where the room temperature moves turbulensitly from 30.8 - 35.1oC. During the drying process, the movement of heat distribution shows the active phenomenon of a convection heat source from the side of the drying chamber which is a spiral-shaped heating design around the drying chamber. The constant temperature is 36 – 38oC which is the hottest temperature that is almost uniform in the drying room. The use of hot water energy from geothermal hot springs can be an alternative continuous and hygienic drying process